Leadership – The Key Element in Improving Quality Management - Iveta Paulová; Miroslava Mĺkva (Kvalita Inovácia Prosperita, 2011)
The present contribution is processed partial results of the survey application of leadership as one of the fundamental principles of quality management in organizations in the Slovak Republic. This survey was conducted in the research project VEGA No. 1/0229/08 Perspectives of quality management development in coherence with requirements of Slovak republic market. Results from the survey were the basis for proposals to improve the quality management in Slovak industrial organizations